2022
DOI: 10.3390/molecules27061924
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Spectrum and Conformational Analysis of Perillartine: Insights into the Structure–Sweetness Relationship

Abstract: We used high-resolution rotational spectroscopy coupled to a laser ablation source to study the conformational panorama of perillartine, a solid synthetic sweetener. Four conformers were identified under the isolation conditions of the supersonic expansion, showing that all of them present an E configuration of the C=N group with respect to the double bond of the ring. The observed structures were verified against Shallenberger–Acree–Kier’s sweetness theory to shed light on the structure–sweetness relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Scale factors ranging from 1.002 to 1.006 show that the predicted values of the rotational constants correspond to the experimental ones. 33,34…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scale factors ranging from 1.002 to 1.006 show that the predicted values of the rotational constants correspond to the experimental ones. 33,34…”
mentioning
confidence: 99%
“…Scale factors ranging from 1.002 to 1.006 show that the predicted values of the rotational constants correspond to the experimental ones. 33,34 We also estimated the relative population of the detected conformers based on the intensities of the rotational transitions and the predicted dipole moments. We found that the G-g+/cc/t and G+g-/cc/t structures have a similar abundance (50% and 40%, respectively), whereas for the Tg+/cc/t structure it is only about 10%.…”
mentioning
confidence: 99%